A CRITICAL REVIEW ON DEEPANIYA MAHAKASHAYA BASED ON THEIR RASAPANCHAK IN RELATION TO NIGHANTU (International Journal of Ayurveda and Pharma Research, 2021)
Importance of Agni has been mentioned univocally in almost all classical treatises in Ayurveda. It has also been mentioned that hypo-functioning Agni is the root cause of every diseases. Agni plays a vital role in maintaining health and balancing the equilibrium of Dosa, Dhatu and Mala. So, to bring the function of Agni to normalcy, besides maintaining proper diet and regimen, Deepaniya drugs are advised. Ten members of Deepaniya mahakashaya are discussed here critically based on their Rasapanchak i.e., Rasa, Guna, Virya, Vipaka and Karma. In this review article a comparative study has been done on Deepaniya mahakashaya as mentioned in Charaka Samhita and discussed in relation to Bhavaprakash Nighantu, Dhanwantari Nighantu, Raj Nighantu and Kaiyadev Nighantu. Along with this, the functions of the drugs mentioned in these classics in the light of modern perspectives are also discussed critically.